Relationship of dental caries and BMI among pre-school children of Bangalore city, India: a cross sectional study - N., Vanishree; Narayan, Rosa R.; N., Naveen; M., Anushri; D., Vignesh; M. P., Neethi Raveendran (International Journal Of Community Medicine And Public Health, 2017)
Background: Dental caries in young children is commonly untreated representing a public health problem and has also reported to affect their anthropometric outcomes, but the evidence is conflicting. Objectives: The aim of this study was to evaluate the relationship between dental caries and BMI in pre-school children of Bangalore City. Methods: A cross-sectional study was conducted on 208 healthy preschool children with the age range of 3-5 years recruited from nursery schools of Bangalore City. The Anthropometric measurements, weight and height were evaluated by calculating the z-scores using WHO Anthro software to elucidate the subject’s status on the age- and sex-specific growth chart. Every Child who has received two Z-scores under the normal value (<-2) was considered as abnormal (deficient). The data was analyzed using Statistical Package for Social Sciences (SPSS) version 19. The statistical tests used were t-test and correlation analysis. Results: Dental caries prevalence was 65.7% with a mean dental caries score of 2.24±2.57. Among the study participants 32.7% were underweight (WAZ score), 46.6% had height deficiency (HAZ score) and 47.6% had BMI deficiency (BAZ score). There was significant positive correlation found between dental caries experience and children’s WAZ (Weight for age) [r=0.102, p=0.040] and BAZ (BMI for age) [r= 0.761, p= 0.032]. Conclusions: This study showed that lesser percentage of the participants had deficient height, weight and BMI. As the weight and BMI increased there was a significant increase in the number of caries and fillings among the participants.